A content-validated interactive medium for basketball skill learning: development using Lectora Inspire - Candra, Oki; Rahmadani, Ahmad; Parulian, Toktong; Fernando, Ricky; Wahyuni, Putri (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2026)
Background: The rapid digital transformation in education necessitates the development of interactive learning media, particularly in physical education domains such as basketball, which require the integration of motor skills, tactical understanding, and active engagement. However, conventional instructional media often fail to adequately support the visual and practical demands of sports learning. Objectives: This study aimed to develop Lectora Inspire–based interactive media for learning basic basketball techniques and to evaluate its content validity using the Content Validity Index (CVI). Methods: A quantitative descriptive validation design was employed involving four expert validators. Data were collected using a structured questionnaire assessing format, content, and language aspects. Content validity was analysed using item-level (I-CVI) and scale-level (S-CVI) indices. Results: The results indicated a high level of agreement among experts, with an overall mean validity score of 88.24%. The S-CVI/Ave reached 0.95, exceeding the recommended threshold of 0.80. Fifteen out of nineteen items achieved an I-CVI of 1.00, while four items (interactive features, visual display quality, audio-video clarity, and sequential organisation) showed I-CVI values of 0.75, indicating the need for revision. Conclusion: The developed interactive media demonstrates strong content validity and provides a structured approach for integrating digital technology into basketball learning. This study contributes by applying a CVI-based validation framework in motor-skill-based instructional media. Future research should examine its effectiveness through experimental designs.